Anti-CD20-Mediated B Cell Depletion Is Associated With Bone Preservation in Lymphoma Patients and Bone Mass Increase in Mice - Kolomansky, Albert; Kaye, Irit; Ben-Califa, Nathalie; Gorodov, Anton; Awida, Zamzam; Sadovnic, Ofer; Ibrahim, Maria; Liron, Tamar; Hiram-Bab, Sahar; Oster, Howard S.; Sarid, Nadav; Perry, Chava; et al. (Frontiers in Immunology, 2020)
Immunotherapy with anti-CD20-specific antibodies (rituximab), has become the standard of care for B cell lymphoproliferative disorders and many autoimmune diseases. In rheumatological patients the effect of rituximab on bone mass yielded conflicting results, while in lymphoma patients it has not yet been described. Here, we used cross-sectional X-ray imaging (CT/PET-CT) to serially assess bone density in patients with follicular lymphoma receiving rituximab maintenance therapy. Remarkably, this treatment prevented the decline in bone mass observed in the control group of patients who did not receive active maintenance therapy. In accordance with these data, anti-CD20-mediated B cell depletion in normal C57BL/6J female mice led to a significant increase in bone mass, as reflected by a 7.7% increase in bone mineral density (whole femur), and a ~5% increase in cortical as well as trabecular tissue mineral density. Administration of anti-CD20 antibodies resulted in a significant decrease in osteoclastogenic signals, including RANKL, which correlated with a reduction in osteoclastogenic potential of bone marrow cells derived from B-cell-depleted animals. Taken together, our data suggest that in addition to its anti-tumor activity, anti-CD20 treatment has a favorable effect on bone mass. Our murine studies indicate that B cell depletion has a direct effect on bone-remodeling.